Decolonizing Cyberspace: Online Support for the Nunavut MEd - McAuley, Alexander; Walton, Fiona (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Offered between 2006 and 2009 and graduating 21 Inuit candidates, the Nunavut Master of Education program was a collaborative effort made to address the erosion of Inuit leadership in the K-12 school system after the creation of Nunavut, Canada’s newest territory, in 1999. Delivered to a large extent in short, intensive, face-to-face courses, the program also made extensive use of online supports. This paper outlines the design challenges – geographical, technological, pedagogical, and cultural – that faced the development and delivery of the online portion of the program. It highlights the intersection of the design decisions with the decolonizing principles that framed the program as a whole, the various and varying roles played by the online environment over the course of the program, and the program’s contribution to student success.